FOREST TYPOLOGICAL CLASSIFICATION SYSTEM AND WAYS OF ITS IMPROVEMENT - Migunova, E. S. (Forestry and Forest Melioration, 2018)
The forest typology as a special direction of theoretical forestry was created on the national knowledge of the forest nature collected by Russian foresters at a turn of the XIX-XX centuries and generalized by G. F. Morozov in the theory of interrelations of the forest and its environment or the theory of the types of plantings. A. A. Krudener, the leading forest manager, who studied the national knowledge like the tales and epics were studied, identified “type of plantation” taxon as a unity of climate, soil and vegetation community and gave the first ever scientific definition of the ecosystem. Following the popular postulate "what is the soil of earth, so is the forest", he developed an interfaced classification of forests and soils, in which the forests are placed on the buildup of soil fertility. P. S. Pogrebnyak transformed the central fragment of the Krudener’s table to the compact classification model in richness (nutrient status) and watering of earth coordinates, called edaphic grid. A number of regulations of this theory require improvement. The type of habitat was called by Vorobyov the type of forest site and identified as the largest taxon. He claimed that at one type of forest site the climate may be different. In different climates there are similar, but not identical types of habitats. Forestry has to be managed taking into account two features of the environmental conditions - the zonality caused by climate and intra-zonal variety connected with the differences of composition and structure (topography) of the surface depositions - and be organized according to the most perfect scenario, on the zonal-typological basis. Forest typology of Morozov-Krudener-Pogrebnyak is an outstanding scientific achievement of Russian and Ukrainian foresters. It is supposed that over time its principles will be the basis for different natural sciences.